The Impact of Reopening Zheng He’s Maritime Silk Road through One Belt One Road Policy on Indonesia–China Cooperation - Adibrata, Jordan Aria; Azis, Azrul; Khairi, Naufal Fikhri (Journal of Integrative International Relations, 2020)
The aim of this article is to explain the impact of reopening the maritime silk route that was previously discovered by Admiral Zheng He which affecting the cooperation relations between Indonesia and China in the last few years. The line was reopened in 2013 in the Chinese OBOR policy with the name “21st Country Maritime Silk Road” (a new maritime silk route) that connects countries in Asia, Africa, and Europe, including Indonesia which in 2017 agreed to participate in inside it. The research question is; "What did Indonesia and China get from the reopening of the maritime silk route through OBOR?". This article used descriptive qualitative methods, using documented research data collection techniques. The results is cooperation between Indonesia and China in the OBOR policy is a form of interdependence.